Self-healing magnetorheological elastomers based on thermoreversible Diels–Alder networks. (2nd March 2023) - Cerdan, Kenneth; Brancart, Joost; Camacho, Guillermo; de Vicente, Juan; Puyvelde, Peter Van
Abstract: Magnetorheological (MR) elastomers are a class of stimuli-responsive materials of which the damping and stiffness can be reversibly tailored by applying magnetic fields. However, concerns such as fatigue damage, insufficient MR efficiencies with low loadings of magnetic particles or highly crosslinked elastomers, and lack of reprocessability remain unaddressed for conventional MR elastomers. To this end, a series of self-healing MR elastomers (SHMRE) were prepared based on thermoreversible Diels–Alder covalent crosslinks. The application of magnetic pulses yielded pre-aligned magnetic particles chains within the curing matrix which strongly influenced the SHMRE rheological properties. The resulting composites do not only exhibit a large MR effect but also efficient self-healing properties at room temperature. We found that the particle loading and the field-induced orientation of the aggregates affect the magnitude of the MR response, the mechanical strength and the healing efficiency. In addition, the MR response is also strongly influenced by the temperature. With a temperature increase from room temperature to 70 °C, a change in the MR response from 90% to 462% is observed while the SHMRE retain a solid viscoelastic state at 50 wt% particles loading. Interestingly, the thermoreversible features of the synthesized networks also allow potential reprocessability of SHMRE when heating these systems above the gel transition temperature (89 °C–90 °C). The final low viscous state makes it possible for the magnetic particles to be potentially restructured as chains by applying a magnetic field, which are retained upon cooling when the solid network state is recovered. The proposed SHMRE systems are shown to be a highly efficient and reprocessable solution to substitute classical MR elastomers in a wider context of generalized MR materials.